2010
DOI: 10.1055/s-0030-1249098
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Levetiracetam for Outpatient Alcohol Detoxification

Abstract: The findings of this study provide some evidence that levetiracetam is an efficacious and safe treatment option for outpatient alcohol detoxification. Further randomised, controlled trials including mid- and long-term follow-ups are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
12
0
1
Order By: Relevance
“…The few available data have shown that the treatment with LEV resulted in a rapid and stable clinical improvement of AWS. Its usefulness in AWS treatment still needs to be investigated 83, 84…”
Section: Therapymentioning
confidence: 99%
“…The few available data have shown that the treatment with LEV resulted in a rapid and stable clinical improvement of AWS. Its usefulness in AWS treatment still needs to be investigated 83, 84…”
Section: Therapymentioning
confidence: 99%
“…Treatment group, age, and number of previous detoxifications (the latter two have been identified as risk factors for alcohol relapse in previous studies) (Beck et al, 2012;Muller et al, 2010) were included into the regression analyses as risk factors. Hazard ratios (HR) with 95 % confidence intervals were determined.…”
Section: Sample Size Calculations and Statistical Analysesmentioning
confidence: 99%
“…Our results suggest that LEV may have clinical utility in the treatment of alcohol use disorders by decreasing alcohol reward, by interfering with the development of neuroadaptations to chronic alcohol, or both. While results from open-label trials of LEV for maintenance of sobriety in alcohol-abusing patients were initially positive (Mariani and Levin, 2008;Sarid-Segal et al, 2008;Müller et al, 2010), recent double-blind placebocontrolled clinical trials have been less convincing (Fertig et al, 2012;Richter et al, 2012). However, the use of LEV as an add-on agent to other pharmacotherapy regimens has not been extensively explored (Müller et al, 2011), but may provide benefit for patients with alcohol abuse disorders.…”
Section: Discussionmentioning
confidence: 99%